Common fragrance and flavor materials : preparation, properties and uses - Surburg, Horst; Panten, Johannes (Wiley-VCH, 2016)
This book presents a survey of those natural and synthetic fragrance and flavor materials which are isolated and produced commercially on a relatively large scale because of their organoleptic characteristics. It provides information on their properties, methods employed in their manufacture, and their areas of application.